L'odyssée de l'Homme en marche: voyage anthropologique Connaissances actuelles et méthodes de recherche - Gaudio, Attilio (Firenze University Press, 2004)
During the second half of the 20th Century he proved to be one of the most ardent defenders of the peoples of the Third World. This anthropological anthology brings together his last three cycles of lectures devoted to ethno-history and methods of work in the field. It is a journey to the heart of man, through the biological and above all cultural evolution of the species, as part of an educational project intended for the study of mankind.